From Erythroblasts to Mature Red Blood Cells: Organelle Clearance in Mammals - Moras, Martina; Lefevre, Sophie D.; Ostuni, Mariano A. (Frontiers in Physiology, 2017)
Erythropoiesis occurs mostly in bone marrow and ends in blood stream. Mature red blood cells are generated from multipotent hematopoietic stem cells, through a complex maturation process involving several morphological changes to produce a highly functional specialized cells. In mammals, terminal steps involved expulsion of the nucleus from erythroblasts that leads to the formation of reticulocytes. In order to produce mature biconcave red blood cells, organelles and ribosomes are selectively eliminated from reticulocytes as well as the plasma membrane undergoes remodeling. The mechanisms involved in these last maturation steps are still under investigation. Enucleation involves dramatic chromatin condensation and establishment of the nuclear polarity, which is driven by a rearrangement of actin cytoskeleton and the clathrin-dependent generation of vacuoles at the nuclear-cytoplasmic junction. This process is favored by interaction between the erythroblasts and macrophages at the erythroblastic island. Mitochondria are eliminated by mitophagy. This is a macroautophagy pathway consisting in the engulfment of mitochondria into a double-membrane structure called autophagosome before degradation. Several mice knock-out models were developed to identify mitophagy-involved proteins during erythropoiesis, but whole mechanisms are not completely determined. Less is known concerning the clearance of other organelles, such as smooth and rough ER, Golgi apparatus and ribosomes. Understanding the modulators of organelles clearance in erythropoiesis may elucidate the pathogenesis of different dyserythropoietic diseases such as myelodysplastic syndrome, leukemia and anemia.